THE EXISTENCE OF SOCIO-ECONOMIC COMMUNITY AROUND GUS DUR FAMILY TOMB IN THE CUKIR VILLAGE YEAR OF 2009-2016 - Mitha Aprilia Kartikaningtyas; Sumarjono Sumarjono; Bambang Soepeno (History Education, University of Jember, 2020)
Social and economic movement in this case is a change in the community around the tomb of Gus Dur at Cukir village years 2009-2016 towards the better. The changes that occurred in the economy is evident impact on income and the improvement of the education of children around the tomb, say previous earnings ranging between Rp. 1,500,000 monthly increase of around Rp. 2,000,000 every weekend. While social changes seen from the kind of occupations, how interact people around the tomb interact to sellers from outside the Cukir village and enterprise spirit of communities around the tomb, for example changes in the type of occupations from agricultural sector into the trade sector. The problems that were examined are: (1) how is the socio-economic conditions before 2009? (2) what are the factors that cause social and economic movement? (3) how the socio-economic movement around the family tomb complex in the village of Gus Dur Cukir years 2009- 2016?. The purpose of this study are: (1) to assess the socio-economic conditions of society before 2009; (2) to examine factors that cause social and economic movement; (3) to assess the socio-economic changes of society around the family tomb complex in the village of Gus Dur Cukir years 2009-2016. This study used heuristic method with the stage of history, criticism, interpretation and historiography. The approach used Economic Sociology and the theory of modernization. Keywords: Socio-Economic Changes, Society Neighborhood Around Gus Dur Tomb